Pengunaan Model Pembelajaran Kooperatif Tipe Tebak Kata dalam Keterampilan Berbicara Bahasa Jerman Siswa - Murniati, Murniati; Muddin, Muddin; Burhanuddin, Burhanuddin (Indonesian Journal of Educational Studies, 2018)
The purpose of this study was to obtain data on the effectiveness of cooperative learning models guessing words in students' speaking skills. This research is a quasi-experimental study. The population of this study was all students of class XI Semen Tonasa High School consisting of 2 classes totaling 97 students. The sample used was Random Sampling, namely students of class XI IPS 2, amounting to 28 students as the experimental class and students of class XI IPS I, amounting to 28 students as the control class. The data obtained were analyzed using the t-test formula. The results of data analysis showed (t count 3.34> t table 0.005 at a significant level of Î± 0.05. The results showed that the cooperative learning model guessed the word effective in the German speaking skills of students.